Adult Stem Cells in the Human Testis - Goossens, Ellen; Tournaye, Herman (Seminars in Reproductive Medicine, 2013)
The primary function of the mammalian testis is the production of both gametes and hormones over a reproductive lifespan. This production of gametes proceeds in the seminiferous tubules and is supported by a stem cell population, the spermatogonial stem cells (SSCs). Like other tissue-specific stem cells, SSCs are defined by their ability to balance between self-renewal and differentiation. This balance maintains the stem cell pool and guarantees the daily production of spermatozoa from puberty onward. Studying SSCs is difficult because they are very few in number (0.03% of all germ cells), and specific markers have not been identified so far. Most of our knowledge results from experiments in rodent models. Very little is known about human SSCs. This review provides an update on SSCs, on their role in male fertility, and on (future) clinical applications using these fascinating cells.
Keywords: male infertility; spermatogenesis; stem cell; transplantation